Design and Implementation of an Indoor light supplement control system based on STM32 microcontroller - Yuan, Fusen; Zhao, Xuchen; Chen, Hao; Ming, Yue; Zhang, Jie (Journal of physics. Conference series, 2020)
At present, most traditional lighting methods use energy conversion methods, which not only causes great harm to the environment, but also has great functional limitations and low solar energy utilization. This paper proposes an indoor adaptive precise light supplement system that can be applied to multiple scenes. This system introduces the hardware and software components of the adaptive and accurate light supplement system from three aspects: the light follow-up system, the light supplement system, and remote monitoring. It realizes the information interaction between users and the system, which significantly improves the accuracy and efficiency of indoor lighting, and has great strategic significance for the full development and utilization of solar energy.